Obesity as a Risk Factor for Failure to Wean from ECMO: A Systematic Review and Meta-Analysis - Syed Arsalan A. Zaidi; Kainat Saleem (Canadian Respiratory Journal)
Purpose. Obesity has been associated with an increased risk of respiratory complications and other systemic illnesses. Respiratory dynamics in an obese patient, combined with modified lung physiology of ARDS, present a significant challenge in managing obese patients with ARDS. Many physicians think of obesity as a relative contraindication to ECMO. We performed a meta-analysis to see the effect of obesity on weaning from ECMO and survival to hospital discharge. Methods. We searched online databases for studies on ECMO and obesity. The search yielded 49 citations in total; after extensive review, six studies were assessed and qualified to be included in the final analysis. Patients were stratified into BMI >30 kg/m2 (obese) and BMI < 30 kg/m2 (nonobese). Results. In meta-analysis, there was a total sample population of 1285 patients, with 466 in the obese group and 819 in the nonobese group. There was no significant difference in weaning from ECMO when compared between obese and nonobese patients, with a risk ratio of 1.03 and 95% confidence interval (CI) of 0.94–1.13 (heterogeneity: chi2 = 7.44, df = 4 (p=0.11), I2 = 46%). There was no significant difference in survival rates between obese and nonobese patients who were treated with ECMO during hospitalization, with a risk ratio of 1.04 and 95% CI of 0.86–1.25 (heterogeneity: Tau2 0.03, chi2 = 14.61, df = 5 (p=0.01), I2 = 66%). Conclusion. Our findings show no significant difference in survival and weaning from ECMO in obese vs. nonobese patients. ECMO therapy should not be withheld from obese patients, as obesity is not a contraindication to ECMO.